Targeted nanoparticles containing the proresolving peptide Ac2-26 protect against advanced atherosclerosis in hypercholesterolemic mice - Fredman, Gabrielle (Sci Transl Med, 2015)
Chronic, nonresolving inflammation is a critical factor in the clinical progression of advanced atherosclerotic lesions. In the normal inflammatory response, resolution is mediated by several agonists, among which is the glucocorticoid-regulated protein called annexin A1. The proresolving actions of annexin A1, which are mediated through its receptor N-formyl peptide receptor 2 (FPR2/ALX), can be mimicked by an amino-terminal peptide encompassing amino acids 2–26 (Ac2-26). Collagen IV (Col IV)–targeted nanoparticles (NPs) containing Ac2-26 were evaluated for their therapeutic effect on chronic, advanced atherosclerosis in fat-fed Ldlr(−/−) mice. When administered to mice with preexisting lesions, Col IV–Ac2-26 NPs were targeted to lesions and led to a marked improvement in key advanced plaque properties, including an increase in the protective collagen layer overlying lesions (which was associated with a decrease in lesional collagenase activity), suppression of oxidative stress, and a decrease in plaque necrosis. In mice lacking FPR2/ALX in myeloid cells, these improvements were not seen. Thus, administration of a resolution-mediating peptide in a targeted NP activates its receptor on myeloid cells to stabilize advanced atherosclerotic lesions. These findings support the concept that defective inflammation resolution plays a role in advanced atherosclerosis, and suggest a new form of therapy.